Book Review - Ackerman, Peter; Kruegler, Christopher; Aspe, Pedro; Naim, Moises; Moore, Lieutenant General Harold G. USA (retired); Galloway, Joseph L.; Fallows, James; Susskind, Lawrence E. (Tufts Archival Research Center, 2005)
Volume 19, Issue 1. Winter/Spring. Strategic Non-Violent Conflict: The Dynamics of People Power in the Twentieth Century. Economic Transformation the Mexican Way. Paper Tigers and Minotaurs: The Politics of Venezuela's Economic Reforms. We Were Soldiers Once... and Young. Looking At the Sun: The Rise of the New East Asian Economic and Political System. Environmental Diplomacy: Negotiating More Effective Global Agreements.